Identification and evolutionary analysis of polycistronic miRNA clusters in domesticated and wild wheat - Singh, Amit Kumar; Singh, Nidhi; Kumar, Sundeep; Kumari, Jyoti; Singh, Rakesh; Gaba, Sonam; Yadav, Mahesh C.; Grover, Monendra; Chaurasia, Shiksha; Kumar, Rajesh (Genomics (San Diego, Calif.), 2020)
MicroRNAs are ~22 nucleotide long non-coding RNAs that regulate gene expression at posttranscriptional level. Genome-wide analysis was performed to identify polycistronic miRNAs from wheat. Total 89 polycistronic miRNAs were identified in bread wheat which were distributed on three component sub-genomes (A = 26, B = 33 and D = 30). Except some, most of the identified polycistronic miRNAs were also present in other cultivated and wild wheat species. Expression of 11 identified polycistronic miRNAs could be validated using previously assembled transcriptomes, RNA-seq/s-RNA seq data of cultivated and wild wheats and RT-PCR. Polycistronic miRNAs orthologs were also localized on rice and Brachypodium genomes. As a case study, we also analyzed molecular evolution of miR395 family polycistrons in wheat. Both tandem and segmental duplications contributed to expansion of miR395 family polycistrons. Our findings provide a comprehensive view on wheat polycitronic miRNAs that will enable their in-depth functional analysis in the future. •Polycitrsonic microRNA (miRNA) loci exist in wheat and these are broadly conserved across the ancestral wheat species.•Expression of 11 polycistronic miRNA loci were validated using previously assembled transcriptomes, deep small RNA sequencing (sRNA-seq) data sets and reverse transcription-polymerase chain reaction (RT-PCR).•miR395 family polycistrons were evolved by duplication and subsequent divergence of an ancestral basic polycitronic unit containing two genes.•Massive loss of nucleotide diversity at majority of the A sub-genome polycistronic miRNA loci during domestication. However, a few polycistronic loci were highly conserved across domesticated and wild wheat.